Substances deposited on an inland plateau, Antarctica - Kokichi Kamiyama; Okitsugu Watanabe (National Institute of Polar Research, 1994)
Various substances are transported over the inland plateau of Antarctica through the atmosphere, and deposited onto the snow surface. The chemical composition of the snow will reflect the transportation process and the amounts of the substances present in the atmospheric environment. Concentrations of some substances show an increasing trend due to interior continental snowfall, suggesting that the interior of the Antarctic continent is under a unique sedimentation environment. This is because the inland plateau, a large continuous snow area, is a long way from the area where the substances in the atmosphere are originating, and there is no simple explanation for the increase in concentration of some of the substances in the falling snow. In this report, the investigations on the snow chemistry on the inland plateau, Antarctica, are briefly reviewed. The concentrations of some substances in snow, for example tritium, have increased on the inland plateau. This was produced both by the local effect over the inland plateau, caused by the extremely low temperature air mass, and by the global circulation through the stratosphere, which transports substances directly from remote areas. By considering the special chemical features of the accumulated snow in the interior of the Antarctic continent, we can more effectively interpret ice and snow cores in our study of the global atmospheric environment.